Implementasi Literasi Informasi dalam Pemenuhan Kebutuhan Informasi Pemustaka di Perpustakaan Kementerian Pendidikan dan Kebudayaan - Sumanti, Dinda Ayu; Fauziah, Kiki (UI Scholars Hub, 2017)
This research discusses the implementation of information literacy in Ministry of Education and Culture Library. The aim of this research is to identify the implementation of information literacy through their program which the library held annually. This is a qualitative approach with case study method. Collection of the data is carried out through depth-interview, observation, and document analysis. Results of the research show that the implementation of information literacy which held by Ministry of Education and Culture Library, planned to support one of their mother-institution’s program called Gerakan Literasi Sekolah (GLS), also to introduce the information literacy concept to the student from elementary to the high school. The implementation program itself consists of some activities such as information literacy workshop, library tour, and an interactive game called ‘treasures hunt’. Although the program still simply packed, positive feedback came from the participant and the perceived benefits makes this program worth to be held again in the future with some improvement to make it more better.